Analysis of Antihypertensive Drug Prescription Patterns in Outpatients at the DTP Cihaurbeuti Health Center Health Service Unit - Nugraha, Tuti Setia; Wahlanto, Panji; Novianty, Elisa (Ad-Dawaa : Journal of Pharmacy, 2025)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal, specifically systolic blood pressure  140 mmHg and/or diastolic blood pressure  90 mmHg. Hypertension is a silent killer, known as a prevalent cardiovascular disease. Hypertension is one of the main factors causing the number one death in the world. The aim of this study was to analyze the pattern of prescribing antihypertensive drugs in UPTD Health of DTP Cihaurbeuti Health Center in the period January-March 2020. The aim of this study was to analyze the pattern of prescribing antihypertensive drugs in UPTD Health of DTP Cihaurbeuti Health Center in the period January-March 2020. With the preparation stage method, study stage, data processing, and analysis. Based on the results obtained in the study, namely the Prescription of antihypertensive drugs at the UPTD DTP Cihaurbeuti Health Center for the period January-March 2020, most of the patients were female (78.37%), aged 56-65 years (45.51%), and suffered from grade 2 hypertension (52.24%). ACEI class drugs (captopril) as much as 1.61%, CCB class (amlodipine) as much as 95.97% and diuretic class (furosemide) as much as 0.85%. Based on the drug class criteria of 100%. Drug type criteria of 100%.